Análise do alinhamento das emissoras de televisão da grande vitória às expectativas das agências de publicidade na veiculação de comerciais - Hamerski, Henrique (2009)
The advertising market is a major driver of consumption and television represents about 60% of these investments. Considering that the broadcast television slowing a battle to win that money for agencies. Besides the relevance of programming to meet the goals of the campaign comes as another element of great importance, and that is the process of serving the commercial created by advertising agencies for their clients. It is this aspect that some broadcasters are highlighted, including winning customers from other stations with larger audiences. It was in this context that the work sought to identify and assess what would be considered relevant by the agency when the purchase of television space. The SERVQUAL model was initially used for this evaluation. However, after the application of statistical techniques as factor analysis and discriminant analysis it was inappropriate as a tool for assessment, making up a new model more suitable for reaching this goal